Unexpected formation of gold nanoflowers by a green synthesis method as agents for a safe and effective photothermal therapy. Issue 41 (10th October 2017) - Yang, Da-Peng; Liu, Xuan; Teng, Choon Peng; Owh, Cally; Win, Khin Yin; Lin, Ming; Loh, Xian Jun; Wu, Yun-Long; Li, Zibiao; Ye, Enyi
Abstract : A green synthesis of gold nanoflowers with photothermal therapeutic potential was achieved by using star fruit juice and gold chloride. Abstract : Star fruit ( Averrhoa carambola ) juice rich in vitamin C and polyphenolic antioxidants was used to synthesize branched gold nanoflowers. These biocompatible and stable gold nanoflowers show strong near-infrared absorption. They are successfully demonstrated to be highly efficient for both in vitro and in vivo photothermal therapy by using an 808 nm laser.